2015
DOI: 10.1177/1077801215590672
|View full text |Cite
|
Sign up to set email alerts
|

To Tell or Not to Tell

Abstract: The underreporting of rape is well known; however, there is less information on women who fail to disclose to anyone. This online study suggests that 24% of 242 women who were non-disclosing compared with those who had disclosed were significantly less likely to seek treatment for emotional injuries. Also, almost two thirds of non-disclosing women believed that the abuse was their fault versus 39.1% of women with prior disclosure. Of clinical interest is that regardless of disclosure pattern, there was no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 34 publications
0
18
1
6
Order By: Relevance
“…Disclosure also was found to be unrelated to short-term psychological adjustment, unless the disclosure was met with a negative reaction, in which case there was an association with poor adjustment [18]. In addition, other research has found no differences in depression and PTSD diagnoses for women who have disclosed vs those who have not, prompting the investigators to speculate that ASA-related trauma occurs irrespective of disclosure [26]. The large proportion of women who report ASA to an informal source points to disclosure as potentially important in post-assault functioning; however, the association between sexual assault disclosure and sexual functioning-a possible outcome of ASA-has not been investigated.…”
Section: Sexual Assault Disclosurementioning
confidence: 97%
“…Disclosure also was found to be unrelated to short-term psychological adjustment, unless the disclosure was met with a negative reaction, in which case there was an association with poor adjustment [18]. In addition, other research has found no differences in depression and PTSD diagnoses for women who have disclosed vs those who have not, prompting the investigators to speculate that ASA-related trauma occurs irrespective of disclosure [26]. The large proportion of women who report ASA to an informal source points to disclosure as potentially important in post-assault functioning; however, the association between sexual assault disclosure and sexual functioning-a possible outcome of ASA-has not been investigated.…”
Section: Sexual Assault Disclosurementioning
confidence: 97%
“…In a second qualitative (case) study of a rural lesbian woman who was raped by a woman, she similarly expressed shame and the need to hide the assault from both the lesbian, gay, bisexual, and transgender and broader community in order to avoid humiliation and scandal (Wang, 2011). In a related vein, an online survey of women (mostly White, educated) who had been raped found that those disclosing for the first time during the survey had higher self-blame than previous disclosers (64% vs. 39%), with first-time disclosers much more likely to have never sought therapy (Carretta, Burgess, & DeMarco, 2015). Indeed, Patterson, Greeson, and Campbell's (2009) qualitative study with a diverse sample of rape survivors who had never disclosed, echoed these findings of self-blame and shame as key barriers: '' .…”
Section: Sa and Self-blame (Behavioral Characterological And General)mentioning
confidence: 99%
“…Researchers often provide lists of local resources and use nonblaming (or antiblaming) wording in materials, instructions, and questions. Gaining insights and receiving tangible aid such as resource lists with anti-blaming language may reduce self-blame, which is associated with survivors disclosing and help-seeking (Carretta, Burgess, & DeMarco, 2015; Kilpatrick, Resnick, Ruggiero, Conoscenti, & McCauley, 2007; Patterson, Greeson, & Campbell, 2009; Starzynski, Ullman, Townsend, Long, & Long, 2007).…”
Section: Benefits Of Participation In Trauma Researchmentioning
confidence: 99%
“…Finally, we expect characteristics that make survivors more likely to disclose or seek help in general will also make them more likely to seek help due to research participation (for reviews of facilitators and barriers of sexual assault disclosure, see Kennedy et al, 2012; Ullman, 2007). Such factors include having more stereotypical assaults involving strangers, violence, injury, or life threat (Orchowski & Gidycz, 2012; Walsh et al, 2015; Wolitzky-Taylor et al, 2011); a history of disclosing to more people or seeking emotional support to cope (Carretta et al, 2015); receiving more positive and fewer negative reactions to disclosure (Ahrens, 2006; Relyea & Ullman, 2015); education; and having a White racial identity as compared with having a African American racial identity or other non-White identities (Kennedy et al, 2012; Starzynski et al, 2007; Ullman, 2007).…”
Section: The Current Studymentioning
confidence: 99%